PENGEMBANGAN APLIKASI REGION BASED EARLY WARNING SYSTEM PENYEBARAN PENYAKIT DEMAM TIFOID BERBASIS SMS GATEWAY DENGAN PENDEKATAN TRIANGULASI - Dewa Made Erdy Kusuma (Universitas Pendidikan Ganesha, 2012)
This study was aimed to design and implement an application that can give early warnings via SMS in case of an outbreak of typhoid fever in the surrounding area. Until now, typhoid fever is still endemic in Indonesia and easily found around us. High body temperature is one characteristic of this disease. The disease was caused by Salmonella typhi bacteria infection that enters the body through the digestive tract. These disease is part of endemic diseases. The concept offered in the provision of a warning message was to consider the extent of the potentially affected by outbreaks of the disease without having to be depended on the complex GIS component, including without involving the position determination like GPS (Global Positioning System) and LBS (Location Based Services). There were three main processes in this system, that were estimating the position of one's home through calculations utilizing triangulation approximation, validating the existence of a fictitious case, and the determination of spreading message radius. The application was developed by using open source Gammu Easy Installer 1.25 as an SMS gateway and PHP 5.2.8 as a programming language. The testing of the system using a fictitious map that created by author. Based on trial results, it is known that the application has been able to give an warning messages of typhoid fever that was built according to design